PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN PROPOSAL PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) BERBASIS PENDAMPINGAN INTENSIF DI SMKN 1 PASAMAN - EDI SUPANRI (STKIP Pesisir Selatan, 2020)
Based on observations of the competencies of teachers at Pasaman 1 Vocational School in preparing Classroom Action Research Proposals, it was found that the teacher's ability to compile classroom action research was still low. The purpose of this study is to describe and obtain information about improving the ability of teachers in preparing Class Action Research Proposals through the CLCK development model (Example, Exercise, Control, Independent Work) Based on Intensive Assistance Based at SMK 1 Pasaman. This research is a school action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 5 teachers of Pasaman 1 SMKN. Research data were collected using observation sheets. Data were analyzed using percentages. Based on the results of research and discussion, it can be concluded that the CLCK development model based on Intensive Assistance can improve the ability of teachers in preparing Classroom Action Research Proposals at SMK 1 Pasaman. Analysis of the quality of PTK proposals made by teachers shows that the teacher's ability to prepare the Classroom Action Research Proposal increases from cycle I to cycle II. The ability of teachers in compiling Classroom Action Research Proposals in cycle I was 71.50 (sufficient) increased to 93.00 (good) in cycle II